Dielectric relaxation dynamics in poly(vinylidene fluoride)/Pb(Zr0·53Ti0.47)O3 composites. (9th September 2020) - Costa, C.M.; Sabater i Serra, R.; Andrio Balado, A.; Gómez Ribelles, J.L.; Lanceros-Méndez, S.
Abstract: Polymer-ceramic composites based on poly(vinylidene fluoride) and ceramic particles of the inorganic piezoelectric material Pb(Zr0 · 53 Ti0.47 )O3 were prepared with different particle concentrations and size by solution casting in the non-polar (α−) and polar (β-) phases of the polymer. The influence of amount and particle size on the overall dielectric response of α- and β-phase matrix composites was analyzed, focusing on the dielectric relaxation processes. The cooperative segmental motions within the PVDF amorphous phase (low-temperature β-relaxation), are strongly affected by the inclusion of the fillers, both in the α− and β-phase matrix composites. The complex permittivity analyzed by the Havriliak-Negami equation model (NH) and the fragility parameter indicates that the PZT ceramic filler induces heterogeneity in the polymer matrix. For α-PVDF/PZT composites, the strength of the relaxation process increases with increasing the filler amount and it is nearly independent on particle size. The behavior of the HN shape parameters, more noticeable for filler content of 20% or higher, shows that the relaxation dynamics is influenced by the polymer nucleation kinetics. PVDF/PZT composites in β-phase matrix exhibit a strong increase in the relaxation strength for PVDF/PZT composites with 40% of ceramic fillers, and the process becomes more symmetric when the amount of filler increases. The detected variations in the relaxation dynamics in both α- and β-phase matrix composites is strongly affected by the ceramic filler and the interface between the ceramic microparticles and the polymer. Graphical abstract: Image 1 Highlights: The dielectric relaxation dynamics of poly(vinylidene fluoride)/Pb(Zr0 · 53 Ti0.47 )O3 composites is evaluated. The dielectric behavior is analyzed as a function of polymer phase, filler amount and size. The dielectric response is analyzed by the Havriliak-Negami model. For filler content of 20% or higher, the relaxation dynamics is affected by changes in the polymer nucleation kinetics. The relaxation dynamics is affected by the ceramic filler and the ceramic/polymer interfaces.